The Spatial Mobility of Hainan Province Women Entrepreneurs in the Context of China’s Economic Fluctuation The Case of Qiongshan - Chen, Minglu (México y la Cuenca del Pacífico, 2015)
Based on interviews in Qiongshan District, Haikou City, Hainan Province in the People’s Republic of China, conducted in 2004-05, this paper examines the spatial mobility of women who have migrated from mainland to Qiongshan to engage in entrepreneurial activity. The paper considers the interviewees’ places of origin, as well as the time and motivation of their migration. Overall, the paper suggests that the movement of women entrepreneurs and their husbands into Hainan has varied in response to fluctuations in the island’s economic fortunes, and in line with adjustments to the legal constraints on population movements imposed by the government.